2019
DOI: 10.1111/psq.12614
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Presidency: Which Presidents Are Uncommonly Successful in Congress? A Trump Update

Abstract: This article updates previous research that seeks to identify which presidents won more or fewer roll-call votes than should be expected through Trump's first two years in office. Multiple regression models estimating the effects of key contextual variables known to influence roll-call voting in Congress (party control, public approval, and party polarization plus interactions) establish a common baseline of predicted success. The errors reveal which presidents won more or less than should be expected given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…7 Table 1 reports results of the regression analysis of annual presidential success rates from 1953 to 2022 (N = 70 years). Results are similar to earlier iterations analyzing fewer presidents (Bond, 2019b;Cohen et al, 2013aCohen et al, , 2013bFleisher et al, 2008;Teodoro & Bond, 2017). 8 These regression models estimate predicted success relative to a common baseline of contextual variables known to influence roll-call voting in Congress.…”
Section: Assessing Presidential Wins Above or Below Expectations A Ba...supporting
confidence: 63%
See 2 more Smart Citations
“…7 Table 1 reports results of the regression analysis of annual presidential success rates from 1953 to 2022 (N = 70 years). Results are similar to earlier iterations analyzing fewer presidents (Bond, 2019b;Cohen et al, 2013aCohen et al, , 2013bFleisher et al, 2008;Teodoro & Bond, 2017). 8 These regression models estimate predicted success relative to a common baseline of contextual variables known to influence roll-call voting in Congress.…”
Section: Assessing Presidential Wins Above or Below Expectations A Ba...supporting
confidence: 63%
“…The label "polar opposite" political styles is not based on a quantitative metric. Yet numerous examples illustrate how Trump's behavior is well outside the normal range observed of past presidents (seeBond, 2019b). Since his behavior is antithetical of any president we have studied, "polar opposite" seems to be a reasonable, if unmeasured, characterization.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Recent scholarly evaluations of Trump's relationship with Congress reveal a contradictory picture of his success in Congress and the extent to which his leadership skills influenced any legislative victories. Trump's success on roll‐call votes was better than predicted (Bond 2019a), and his success rate in 2017 was the highest of any recent president (CQ Almanac 2017). Indeed, the data show a high rate of success for Trump in Congress before the 2018 midterm elections, generating an overall success rate of 98.3% in 2017 and 93.4% in 2018, according to Congressional Quarterly's analysis of roll‐call votes.…”
Section: Trump's Rhetoric In Relation To Congress and The Publicmentioning
confidence: 92%
“…The increasingly conservative views of Republican senators and the president’s support among their constituents are the most likely explanations. Jon Bond found that Trump did about what one would expect in the political environment in which he operated (Bond 2019).…”
Section: Congressional Supportmentioning
confidence: 99%